Cultivation of human mesenchymal stem cells in animal serum free conditions - Škifić, Marijana; Golemović, Mirna; Mazić, Sanja Bojanić, Ines; Davidović Mršić, Sanja Franić Simić, Ivana; Sučić, Mirna Ilić, Ivana; Batinić, Drago Serventi Seiwerth, Ranka; Labar, Boris Golubić Čepulić, Branka (2009)
Human mesenchymal stem cells (hMSCs) are nonhematopoietic multipotent stem cells. Although they are present in various organs and tissues they are mainly residing in the bone marrow (BM). MSCs have been shown to express immunomodulatory properties in vitro, like inhibiting T-cell proliferation after stimulation by alloantigens and mitogens and by preventing the activity of cytotoxic T cells. Since they are also immunoprivileged cells that could be transplanted across MHC barriers, their considerable therapeutic potential has generated increasing interest in the field of cellular therapy. So far, hMSCs have been clinically applied to facilitate engraftment in hematopoietic stem cell transplantation (HSCT) and to treat acute graft versus host disease (aGVHD). Since incidence of hMSCs in BM is only ~1 per 104 nucleated cells, ex vivo expansion of these cells is necessary. Clinical application requires 2x106 hMSCs/kg per adult patient. So far the most successful culture conditions for hMSCs expansion ex vivo included use of fetal bovine serum (FBS), which represents the potential risk of prion transmission and immunological reactions. For these reasons, there is a great interest in search for an FBS substitute and platelet lysate (PL) has been recently proposed. The aim of this study was to evaluate the hMSCs cultured in FBS-free culture conditions. Mononuclear cells (MNC) were isolated from BM sample of healty donor with a Ficoll density gradient centrifugation and plated at 100 000/cm2 in -MEM culture medium containing 10%FBS or 5%PL. PL was obtained from a single allogenic platelet unit prepared by the Hospital Transfusion Center. At subconfluency, cells were harvested after Trypsin-EDTA treatment and subsequently replated at 1000 hMSCs/cm2 until reaching passage 5. To evaluate the clonogenic potential of cultured hMSCs colony-forming unit-fibroblast (CFU-F) assays were performed at each passage. The characteristic immunophenotype was assesed by flow cytometry. To assess their multipotential capacity, hMSCs were induced into adipogenesis at passage 3. hMSCs were also analyzed for chromosomal stability at passages 4 and 5 to validate their safety for potential use as a cell therapy product. Our results showed that hMSCs were successfully cultured in media supplemented with PL. hMSCs cultured in that condition demonstrated lower increase in cell number and CFU-F colonies compared to cells cultured in the presence of FBS. Therefore the addition of bFGF (basic fibroblast growth factor) should be considered in the future expansion experiments. hMSCs expanded in PL condition expressed all known characteristics of cultured MSCs ; adherence to plastic, expression of CD105 and EMBO Young Scientist Forum Zagreb University, Croatia June 15-17, 2009. 49 CD90 and in specific culture condition they were able to differentiate into adipocytes. Although most of analyzed metaphases in passage 4 had a normal karyotype, some of metaphases carried trisomy 8 which was not detected in following passage (p5). Karyotype anomalies are already described in the literature and since they are not stable and sustainable in later passages they appeared not to have selective advantage in the culture system and therefore are not of pathological nature. This study provides a basis for further
Projekt MZOS
Projekt MZOS
ENG